Ceramic tile adhesive and method of making same
Patent Information
- Application Number
- CN202410409468.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-07
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-04-07
AI Technical Summary
[0022](1)通过向瓷砖胶中加入普通硅酸盐水泥、石英砂作为瓷砖胶的主要骨料成分,增加瓷砖胶的黏性和粘结力,使其更容易紧密地附着于基层上。石英砂使得铺设的瓷砖更加牢固耐用。加入粉煤灰以提高瓷砖与基层之间的结合力和黏合力。增加瓷砖胶的柔韧性,防止瓷砖产生裂缝。加入纤维素醚能够进一步提高瓷砖胶的粘结性能,提高瓷砖胶的抗滑移性和粘贴牢固度。硅酸镁铝能够提高瓷砖胶使用时的施工爽滑性。淀粉醚能够起到快速增稠的作用,使瓷砖与基材之间的贴合更加牢固,同时改善瓷砖胶的流动性,让瓷砖胶更好地涂抹在墙面上。同时还添加了胶粘增强剂,进一步提高瓷砖胶的粘结性,同时能够明显改善瓷砖胶在不同温度下发生热胀冷缩时的粘结强度,多孔纳米材料的添加分散了瓷砖胶热胀冷缩产生的应力,在不同热膨胀系数的组分之间起到缓冲的作用,避免了不同组分热胀冷缩产生不同的应力而导致瓷砖胶的开裂甚至脱落。
Smart Images

Figure BDA0004778636020000131
Abstract
Description
Technical Field
[0001] This application relates to the field of building materials technology, and in particular to a tile adhesive and its preparation method. Background Technology
[0002] Tile adhesive is a modern building material used for bonding ceramic tiles, facing bricks, floor tiles, and other decorative materials. It is widely applicable to interior and exterior walls, floors, bathrooms, kitchens, and other architectural surfaces. In recent years, with the vigorous development of the building decoration industry, the use and decorative application of ceramic tiles have been increasing, and the tile adhesive market has shown a steady growth trend.
[0003] The tile adhesive currently in use has low heat resistance and bonding strength. This means that when tiles expand and contract with temperature changes (especially during winter and summer), the tile adhesive lacks sufficient bonding strength to release the internal stress generated by the thermal expansion and contraction of the tiles. After a few years of use, small cracks will appear between the tile adhesive and the tiles. When these cracks accumulate to a certain number, they will gradually form hollow areas and eventually lead to detachment, posing a significant risk to normal use. Summary of the Invention
[0004] This application provides a tile adhesive and its preparation method to solve the problems mentioned in the background art.
[0005] On one hand, this application provides a tile adhesive comprising the following components in parts by weight:
[0006] 50-60 parts by weight of quartz sand, 38-42 parts by weight of ordinary silicate cement, 1.5-2.5 parts by weight of fly ash, 0.8-1.2 parts by weight of workability enhancer, 0.5-0.8 parts by weight of early strength agent, 0.2-0.8 parts by weight of cellulose ether, 0.04-0.1 parts by weight of magnesium aluminum silicate, 0.04-0.06 parts by weight of starch ether, and 0.03-0.07 parts by weight of adhesive enhancer.
[0007] The adhesive reinforcing agent comprises latex powder, 3-amino-2,2-dimethylpropionamide, and porous nanomaterials in a weight ratio of 1:0.5-0.8:0.3-0.6.
[0008] Optionally, the quartz sand includes quartz sand with a fineness of 30-50 mesh and quartz sand with a fineness of 60-80 mesh, and the weight ratio of 30-50 mesh quartz sand to 60-80 mesh quartz sand is 0.75-1:1.
[0009] Optional, the ordinary Portland cement is 42.5R ordinary Portland cement.
[0010] Optionally, the cellulose ether is one or more of methyl cellulose ether, carboxymethyl cellulose ether, carboxypropyl methyl cellulose ether, or carboxyethyl cellulose ether.
[0011] Optional workability enhancers include lignocellulosic fibers and sodium gluconate in a weight ratio of 1:0.7-1.
[0012] Optional early-strength agents include calcium formate, calcium chloride, or triethanolamine.
[0013] On the other hand, this application provides a method for preparing the above-mentioned tile adhesive, comprising the following steps:
[0014] (1) Obtaining porous nanomaterials: 2,5-diamino-benzo-dithiazole was added to the reactor. Under stirring, N,N-dimethylformamide and triethanolamine were added to the reactor to form a dispersion. The dispersion was ultrasonically treated for 10-15 min, and then cyanuric chloride was added. The mixture was ultrasonically treated again for 10-20 min to obtain the slurry to be reacted. The slurry to be reacted was reacted at a temperature of 90-130℃ for 10-14 h to obtain crude porous nanomaterials. The crude porous nanomaterials were washed multiple times to obtain porous nanomaterials.
[0015] (2) Obtaining adhesive reinforcing agent: The porous nanomaterial, latex powder and 3-amino-2,2-dimethylpropionamide are mixed in a weight ratio to obtain adhesive reinforcing agent.
[0016] (3) Obtaining tile adhesive: Mix quartz sand, ordinary silicate cement, fly ash, workability enhancer, early strength agent, cellulose ether, magnesium aluminum silicate, starch ether and adhesive enhancer according to the weight parts for 5-10 minutes to obtain tile adhesive.
[0017] Optionally, the weight ratio of cyanuric chloride, 2,5-diamino-benzo-dithiazole, triethanolamine and N,N-dimethylformamide is 1:2.5-3:2.0-2.5:50-80.
[0018] Optionally, in the preparation steps of porous nanomaterials, the crude porous nanomaterials are washed multiple times, including:
[0019] The crude porous nanomaterial was centrifuged to obtain a precipitate. The precipitate was washed alternately with deionized water and ethanol and centrifuged 3-5 times. The washed precipitate was then freeze-dried to obtain the porous nanomaterial.
[0020] Optionally, the average particle size of the latex powder is 0.2-0.4 μm.
[0021] The tile adhesive and its preparation method provided in this application realize the production of tile adhesive, and compared with the prior art, it has the following beneficial effects:
[0022] (1) By adding ordinary silicate cement and quartz sand as the main aggregate components to the tile adhesive, the adhesiveness and bonding strength are increased, making it easier to adhere tightly to the substrate. Quartz sand makes the laid tiles more secure and durable. Fly ash is added to improve the bonding and adhesion between the tiles and the substrate. It also increases the flexibility of the tile adhesive and prevents cracking. The addition of cellulose ether further improves the bonding performance of the tile adhesive, enhancing its anti-slip properties and adhesion strength. Magnesium aluminum silicate improves the smoothness of the tile adhesive during application. Starch ether acts as a rapid thickener, making the adhesion between the tiles and the substrate stronger, while also improving the fluidity of the tile adhesive, allowing it to be better applied to the wall surface. In addition, adhesive enhancers are added to further improve the adhesion of tile adhesive. They can also significantly improve the bonding strength of tile adhesive when it expands and contracts with temperature. The addition of porous nanomaterials disperses the stress generated by the thermal expansion and contraction of tile adhesive, and plays a buffering role between components with different coefficients of thermal expansion, avoiding cracking or even falling off of tile adhesive caused by different stresses generated by the thermal expansion and contraction of different components.
[0023] (2) By adding an early-strength agent, the hydration rate of ordinary silicate cement is accelerated, promoting the formation of early strength of tile adhesive, significantly improving the adhesion and cohesion of tile adhesive, and speeding up construction. Furthermore, triethanolamine has both early-strength and water-reducing / strengthening functions.
[0024] (3) By using a solvothermal method to synthesize porous nanomaterials and freeze-drying the porous nanomaterials to maintain their porosity as much as possible, and adding them to tile adhesive, the adhesion of the tile adhesive is improved while the stress generated by the thermal expansion and contraction of the tile adhesive is dispersed. It plays a buffering role between components with different coefficients of thermal expansion, which can significantly improve the bonding strength of the tile adhesive when thermal expansion and contraction occurs at different temperatures, and avoid the cracking or even falling off of the tile adhesive caused by different stresses generated by the thermal expansion and contraction of different components. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application are described clearly and completely below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are also within the scope of protection of this application.
[0026] On one hand, this application provides a tile adhesive comprising the following components in parts by weight:
[0027] 50-60 parts by weight of quartz sand, 38-42 parts by weight of ordinary silicate cement, 1.5-2.5 parts by weight of fly ash, 0.8-1.2 parts by weight of workability enhancer, 0.5-0.8 parts by weight of early strength agent, 0.2-0.8 parts by weight of cellulose ether, 0.04-0.1 parts by weight of magnesium aluminum silicate, 0.04-0.06 parts by weight of starch ether, and 0.03-0.07 parts by weight of adhesive enhancer.
[0028] The adhesive reinforcing agent comprises latex powder, 3-amino-2,2-dimethylpropionamide, and porous nanomaterials in a weight ratio of 1:0.5-0.8:0.3-0.6.
[0029] Specifically, tile adhesive is a new material used for bonding decorative materials such as ceramic tiles, facing bricks, and floor tiles. Ordinary silicate cement, commonly used for bonding building materials in construction, is the main component of tile adhesive. Quartz sand, as aggregate, prevents hollow areas and cracking during installation and increases the adhesive's stickiness and bonding strength, making it easier to adhere tightly to the substrate. Furthermore, quartz sand is derived from nature, is pollution-free, harmless to human health, and possesses excellent mechanical strength and wear resistance, resulting in a long service life and making the laid tiles more secure and durable.
[0030] Ordinary silicate cement is a hydraulic cementitious material that conforms to the national standard GB175-2007 and is made by grinding silicate cement clinker, 5%-20% of mixed materials and an appropriate amount of gypsum.
[0031] Fly ash is a solid residue left after dust removal from coal-fired power plant emissions. Its main components are silicate, alumina, and calcium oxide, and it possesses good activity and self-adhesive properties. Adding an appropriate amount of fly ash can effectively improve the performance of tile adhesive, enhancing the bond and adhesion between the tile and the substrate. Fly ash also has a slight expansion effect, increasing the flexibility of the tile adhesive and preventing tile cracking. However, because of this slight expansion property, the amount of fly ash used should be controlled; excessive use can easily lead to tile detachment or cracking.
[0032] Workability enhancers improve the operability of each construction step, including flowability, cohesiveness, and water retention, making it easier for workers to apply tile adhesive when laying tiles. Accelerators improve the early mechanical properties of the tile adhesive, facilitating early bonding between the adhesive and the substrate, and accelerating construction. Cellulose ethers further enhance the adhesive properties of the tile adhesive, improving its anti-slip properties and bonding strength. Magnesium aluminum silicate improves the smoothness of the tile adhesive during application. Starch ethers act as a rapid thickener, ensuring a stronger bond between the tile and the substrate, while also improving the adhesive's flowability, allowing for better application on walls, and enhancing its lubricity, making it smoother and easier to apply. It is crucial to control the amount of starch ether used to 0.04-0.06 parts by weight. Excessive starch ether will increase the viscosity of the tile adhesive, hindering application and delaying drying time; insufficient starch ether will reduce the adhesive's bonding strength and extensibility, affecting tile quality.
[0033] Adhesive enhancers can further improve the adhesion of tile adhesives and significantly improve the bonding strength of tile adhesives when they expand and contract at different temperatures. The latex powder is a redispersible latex powder, which has good adhesion when dispersed in water. During use, the latex powder can disperse into the gaps between ordinary silicate cement and quartz sand skeleton, further bonding ordinary silicate cement, quartz sand aggregate and fly ash together, thereby improving the overall bonding strength of tile adhesives. Simultaneously, porous nanomaterials are added. These nanomaterials have a regularly arranged pore structure with strong adsorption properties. This allows them to adsorb ordinary silicate cement, quartz sand aggregate, fly ash, and latex powder in the tile adhesive during use, trapping these particles inside and on the surface of the pores. These nanomaterials fill the pores of the porous nanomaterials, which are then evenly dispersed within the adhesive, forming an interwoven network structure. This not only binds the components together but also further strengthens the cohesive properties of the adhesive, creating a unified internal force and improving the adhesiveness of the tile adhesive.
[0034] Furthermore, tile adhesive is used in environments with varying temperatures. When the ambient temperature is too high, the different components in the tile adhesive experience different stresses due to thermal expansion and contraction. This can cause the molecular bonds within the ordinary silicate cement, quartz sand aggregate, fly ash, and latex powder in the tile adhesive to break, leading to structural fragmentation and cross-linking breaks in the adhesive components. This results in cracking or a decrease in the mechanical properties of the tile adhesive, ultimately weakening its adhesion. Adding porous nanomaterials allows the components in the tile adhesive to enter the pores of the nanomaterials. The interwoven network structure connects and binds the components, forming a cohesive whole. When the ambient temperature changes, the tile adhesive expands and contracts due to temperature variations. The numerous pores effectively accommodate components with high coefficients of thermal expansion. Simultaneously, the interwoven network structure of the porous nanomaterials disperses the stress generated by thermal expansion and contraction, acting as a buffer between components with different coefficients of thermal expansion. This prevents the tile adhesive from cracking or even detaching due to varying stresses caused by the thermal expansion and contraction of different components. The addition of porous nanomaterials disperses and buffers the stress generated by the components when the temperature changes, improving the adhesion of the tile adhesive and its adaptability to different temperature environments, thus making the tile adhesive widely applicable.
[0035] Simultaneously, 3-amino-2,2-dimethylpropionamide is added to the adhesive reinforcing agent. 3-amino-2,2-dimethylpropionamide provides amide and amino groups, and its nitrogen atoms have good activity, capable of reacting with the active groups in porous nanomaterials, ordinary silicate cement, quartz sand aggregate, fly ash, and latex powder, respectively. This further enhances the connection between ordinary silicate cement, quartz sand aggregate, fly ash, latex powder, and porous nanomaterials, allowing each component to enter the pores of the porous nanomaterials while also adsorbing onto the surface of the porous nanomaterials. This improves the bonding between the components of the tile adhesive, thereby enhancing the overall adhesion of the tile adhesive. It also improves the dispersion and buffering of internal stress generated by the porous nanomaterials during temperature changes, further preventing cracking or detachment of the tile adhesive.
[0036] The latex powder is a redispersible latex powder, specifically a copolymer of ethylene / vinyl acetate, a copolymer of vinyl acetate / ethylene tert-carbonate, or a copolymer of acrylic acid.
[0037] This application achieves the production of tile adhesive through the above-mentioned scheme. By adding ordinary silicate cement and quartz sand as the main aggregate components of the tile adhesive, the adhesive's viscosity and bonding strength are increased, making it easier to adhere tightly to the substrate. Quartz sand makes the laid tiles more secure and durable. Adding fly ash improves the bonding and adhesion between the tile and the substrate. It also increases the flexibility of the tile adhesive, preventing tile cracking. Adding cellulose ether further improves the adhesive's bonding performance, enhancing its anti-slip properties and bonding strength. Magnesium aluminum silicate improves the smoothness of the tile adhesive during application. Starch ether acts as a rapid thickener, making the adhesion between the tile and the substrate stronger, while also improving the adhesive's flowability, allowing it to be better applied to the wall surface. In addition, an adhesive enhancer is added to further improve the adhesion of the tile adhesive. It can also significantly improve the bonding strength of the tile adhesive when it expands and contracts with temperature. The addition of porous nanomaterials disperses the stress generated by the thermal expansion and contraction of the tile adhesive, and plays a buffering role between components with different coefficients of thermal expansion. This avoids the different stresses generated by the thermal expansion and contraction of different components, which can lead to cracking or even detachment of the tile adhesive, and thus prevent the formation of hollow areas in the tile adhesive.
[0038] Optionally, the quartz sand includes quartz sand with a fineness of 30-50 mesh and quartz sand with a fineness of 60-80 mesh, and the weight ratio of 30-50 mesh quartz sand to 60-80 mesh quartz sand is 0.75-1:1.
[0039] Specifically, quartz sand can increase the adhesiveness and bonding strength of tile adhesive, while also improving its strength. Coarser quartz sand is better at improving the strength of tile adhesive, while finer quartz sand is better at promoting its bonding properties. Therefore, mixing quartz sand of different finenesses can jointly promote the strength and bonding properties of tile adhesive.
[0040] Optional, the ordinary Portland cement is 42.5R ordinary Portland cement.
[0041] Specifically, ordinary Portland cement, as the base component of the adhesive, provides the main bond strength. 42.5R ordinary Portland cement is not only beneficial to the adhesion of tile adhesive, but also easy for operators to carry out construction during use.
[0042] Optionally, the cellulose ether is one or more of methyl cellulose ether, carboxymethyl cellulose ether, carboxypropyl methyl cellulose ether, or carboxyethyl cellulose ether.
[0043] Specifically, cellulose ethers can improve the adhesion of tile adhesive. Cellulose ether molecules themselves have strong adsorption and adhesion properties, forming a uniform adsorption layer on the tile adhesive surface, thereby increasing the adhesion between the tile and the substrate. Furthermore, cellulose ethers can improve the rheological properties of tile adhesive, increase its ductility, reduce shrinkage deformation, and enhance its stability and bonding strength.
[0044] Optional workability enhancers include lignocellulose and sodium gluconate in a weight ratio of 1:0.7-1.
[0045] Specifically, wood fiber is a natural fiber, differing from synthetic fibers in fiber structure and chemical composition. Adding appropriate wood fiber can effectively enhance the adhesion and flexibility of tile adhesive, while also improving its tensile and shear strength, mechanical strength, durability, and reliability. Sodium gluconate is used in the concrete industry as a highly efficient retarder and water-reducing agent, significantly improving concrete workability, reducing slump loss, and enhancing the later-stage strength of tile adhesive.
[0046] Optional early-strength agents include calcium formate, calcium chloride, or triethanolamine.
[0047] Specifically, the main function of early-strength agents is to accelerate the hydration rate of ordinary silicate cement, promote the formation of early strength in tile adhesive, significantly improve the bonding strength and cohesion of tile adhesive, and speed up construction. Furthermore, triethanolamine possesses both early-strength properties and certain water-reducing and strengthening functions.
[0048] On the other hand, this application provides a method for preparing the above-mentioned tile adhesive, comprising the following steps:
[0049] (1) Obtaining porous nanomaterials: 2,5-diamino-benzo-dithiazole was added to the reactor. Under stirring, N,N-dimethylformamide and triethanolamine were added to the reactor to form a dispersion. The dispersion was ultrasonically treated for 10-15 min, and then cyanuric chloride was added. The mixture was ultrasonically treated again for 10-20 min to obtain the slurry to be reacted. The slurry to be reacted was reacted at a temperature of 90-130℃ for 10-14 h to obtain crude porous nanomaterials. The crude porous nanomaterials were washed multiple times to obtain porous nanomaterials.
[0050] (2) Obtaining adhesive reinforcing agent: The porous nanomaterial, latex powder and 3-amino-2,2-dimethylpropionamide are mixed in the weight ratio to obtain adhesive reinforcing agent.
[0051] (3) Obtaining tile adhesive: Mix quartz sand, ordinary silicate cement, fly ash, workability enhancer, early strength agent, cellulose ether, magnesium aluminum silicate, starch ether and adhesive enhancer according to the weight parts for 5-10 minutes to obtain tile adhesive.
[0052] Specifically, porous nanomaterials were synthesized using a solvothermal method with N,N-dimethylformamide as the solvent. First, 2,5-diamino-benzo-dithiazole and N,N-dimethylformamide were stirred and mixed, triethanolamine was added as a catalyst, and then cyanuric chloride was added. Simultaneously, ultrasonic treatment was employed to improve the dispersibility of the reactants and to obtain a slurry. The slurry was sealed in a reaction vessel and reacted at 90-130℃ for 10-14 hours to obtain crude porous nanomaterials. Sealing the slurry was necessary because the high-temperature reaction generated high pressure; without sealing, the reactants would spray out, thus ensuring a smooth and safe reaction. The crude porous nanomaterials were then washed multiple times to remove residual raw materials and other impurities, and dried to obtain the porous nanomaterials. The porous nanomaterials, latex powder, and 3-amino-2,2-dimethylpropionamide were then mixed in a specific weight ratio to obtain an adhesive reinforcing agent. Finally, the quartz sand, ordinary silicate cement, fly ash, workability enhancer, early strength agent, cellulose ether, magnesium aluminum silicate, starch ether, and adhesive enhancer are mixed according to their weight proportions for 5-10 minutes to obtain tile adhesive.
[0053] Optionally, the weight ratio of cyanuric chloride, 2,5-diamino-benzo-dithiazole, triethanolamine and N,N-dimethylformamide is 1:2.5-3:2.0-2.5:50-80.
[0054] Specifically, N,N-dimethylformamide is used as a solvent, and the amount added is based on fully dispersing the reaction raw materials. The weight ratio of 2,5-diamino-benzo-dithiazole to cyanuric chloride can ensure that 2,5-diamino-benzo-dithiazole is grafted onto cyanuric chloride, while avoiding excessive use that would lead to waste and subsequent washing processes.
[0055] Optionally, in the preparation steps of porous nanomaterials, the crude porous nanomaterials are washed multiple times, including:
[0056] The crude porous nanomaterial was centrifuged to obtain a precipitate. The precipitate was washed alternately with deionized water and ethanol and centrifuged 3-5 times. The washed precipitate was then freeze-dried to obtain the porous nanomaterial.
[0057] Specifically, impurities in the crude porous nanomaterials are washed with deionized water and ethanol, followed by centrifugation after each wash. The precipitate is then washed again, and this process is repeated 3-5 times to obtain the porous nanomaterials. Freeze-drying helps to preserve the structure and porosity of the porous nanomaterials as much as possible.
[0058] Optionally, the average particle size of the latex powder is 0.2-0.4 μm.
[0059] Specifically, latex powder has good adhesion. During use, latex powder can disperse into the gaps between ordinary silicate cement and quartz sand skeleton, further bonding ordinary silicate cement, quartz sand aggregate and fly ash together, improving the overall bonding strength of tile adhesive, and also increasing the stability and water resistance of tile adhesive, ensuring that the tiles are completely fixed to the base layer after laying, and ensuring their long service life.
[0060] The technical solution of this application will be illustrated in detail below with specific embodiments.
[0061] Example 1
[0062] A tile adhesive and its preparation method, comprising the following steps:
[0063] (1) Obtaining porous nanomaterials: 2,5-Diamino-benzo-dithiazole was added to a reaction vessel. Under stirring, N,N-dimethylformamide and triethanolamine were added sequentially to form a dispersion. The dispersion was ultrasonically treated for 10 min, followed by the addition of cyanuric chloride and ultrasonic treatment for another 10 min to obtain a slurry to be reacted. The slurry was reacted at 90℃ for 10 h to obtain crude porous nanomaterials. The crude porous nanomaterials were centrifuged to obtain a precipitate. The precipitate was washed alternately with deionized water and ethanol and centrifuged 3-5 times. The washed precipitate was dispersed in deionized water and then frozen. The precipitate and the frozen deionized water were freeze-dried to obtain porous nanomaterials. The volume ratio of the washed precipitate to deionized water was 1:2-3, and the freeze-drying conditions were -40-50℃ and 5-10 Pa.
[0064] The weight ratio of cyanuric chloride, 2,5-diamino-benzo-dithiazole, triethanolamine and N,N-dimethylformamide is 1:2.5:2.0:50.
[0065] (2) Obtaining adhesive reinforcing agent: The porous nanomaterial, latex powder and 3-amino-2,2-dimethylpropionamide are mixed in a weight ratio of 1:0.5:0.3 to obtain adhesive reinforcing agent.
[0066] The latex powder is an acrylic copolymer with an average particle size of 0.3 μm.
[0067] (3) Obtaining tile adhesive: Quartz sand, ordinary silicate cement, fly ash, workability enhancer, early strength agent, cellulose ether, magnesium aluminum silicate, starch ether and adhesive enhancer are mixed according to the weight parts for 5 minutes to obtain tile adhesive.
[0068] The amounts of each component are as follows: 50 parts by weight of quartz sand, 38 parts by weight of 42.5R ordinary Portland cement, 1.5 parts by weight of fly ash, 0.8 parts by weight of workability enhancer, 0.5 parts by weight of early strength agent, 0.2 parts by weight of cellulose ether, 0.04 parts by weight of magnesium aluminum silicate, 0.04 parts by weight of starch ether, and 0.03 parts by weight of adhesive enhancer.
[0069] The weight ratio of 30-50 mesh quartz sand to 60-80 mesh quartz sand is 0.75:1. The workability enhancer includes wood fiber and sodium gluconate in a weight ratio of 1:0.7. The cellulose ether is methyl cellulose ether, and the early strength agent is calcium formate.
[0070] Example 2
[0071] A tile adhesive and its preparation method, comprising the following steps:
[0072] The difference from Example 1 is that:
[0073] (3) Obtaining tile adhesive: Quartz sand, ordinary silicate cement, fly ash, workability enhancer, early strength agent, cellulose ether, magnesium aluminum silicate, starch ether and adhesive enhancer are mixed according to the weight parts for 7 minutes to obtain tile adhesive.
[0074] The amounts of each component are as follows: 53 parts by weight of quartz sand, 39.5 parts by weight of 42.5R ordinary Portland cement, 1.8 parts by weight of fly ash, 0.98 parts by weight of workability enhancer, 0.6 parts by weight of early strength agent, 0.4 parts by weight of cellulose ether, 0.06 parts by weight of magnesium aluminum silicate, 0.05 parts by weight of starch ether, and 0.04 parts by weight of adhesive enhancer.
[0075] The weight ratio of 30-50 mesh quartz sand to 60-80 mesh quartz sand is 0.8:1. The workability enhancer includes wood fiber and sodium gluconate in a weight ratio of 1:0.8. The cellulose ether is methyl cellulose ether, and the early strength agent is calcium formate.
[0076] Example 3
[0077] A tile adhesive and its preparation method, comprising the following steps:
[0078] The difference from Example 1 is that:
[0079] (3) Obtaining tile adhesive: Quartz sand, ordinary silicate cement, fly ash, workability enhancer, early strength agent, cellulose ether, magnesium aluminum silicate, starch ether and adhesive enhancer are mixed according to the weight parts for 10 minutes to obtain tile adhesive.
[0080] The amounts of each component are as follows: 57 parts by weight of quartz sand, 41 parts by weight of 42.5R ordinary Portland cement, 2.2 parts by weight of fly ash, 1 part by weight of workability enhancer, 0.7 parts by weight of early strength agent, 0.6 parts by weight of cellulose ether, 0.08 parts by weight of magnesium aluminum silicate, 0.06 parts by weight of starch ether, and 0.06 parts by weight of adhesive enhancer.
[0081] The weight ratio of 30-50 mesh quartz sand to 60-80 mesh quartz sand is 0.9:1. The workability enhancer includes wood fiber and sodium gluconate in a weight ratio of 1:0.9. The cellulose ether is methyl cellulose ether, and the early strength agent is calcium formate.
[0082] Example 4
[0083] A tile adhesive and its preparation method, comprising the following steps:
[0084] The difference from Example 1 is that:
[0085] (3) Obtaining tile adhesive: Quartz sand, ordinary silicate cement, fly ash, workability enhancer, early strength agent, cellulose ether, magnesium aluminum silicate, starch ether and adhesive enhancer are mixed according to the weight parts for 10 minutes to obtain tile adhesive.
[0086] The amounts of each component are as follows: 60 parts by weight of quartz sand, 42 parts by weight of 42.5R ordinary Portland cement, 2.5 parts by weight of fly ash, 1.2 parts by weight of workability enhancer, 0.8 parts by weight of early strength agent, 0.8 parts by weight of cellulose ether, 0.1 parts by weight of magnesium aluminum silicate, 0.06 parts by weight of starch ether, and 0.07 parts by weight of adhesive enhancer.
[0087] The weight ratio of 30-50 mesh quartz sand to 60-80 mesh quartz sand is 1:1. The workability enhancer includes wood fiber and sodium gluconate in a weight ratio of 1:1. The cellulose ether is methyl cellulose ether, and the early strength agent is calcium formate.
[0088] Example 5
[0089] A tile adhesive and its preparation method, comprising the following steps:
[0090] The difference from Example 3 is that:
[0091] (1) Obtaining porous nanomaterials: 2,5-diamino-benzo-dithiazole was added to the reactor. Under stirring, N,N-dimethylformamide and triethanolamine were added to the reactor to form a dispersion. After ultrasonic treatment of the dispersion for 15 min, cyanuric chloride was added and ultrasonic treatment was performed again for 20 min to obtain the slurry to be reacted. The slurry to be reacted was reacted at 110℃ for 12 h to obtain crude porous nanomaterials. The crude porous nanomaterials were centrifuged to obtain precipitates. The precipitates were washed alternately with deionized water and ethanol and centrifuged 3-5 times. The washed precipitates were freeze-dried to obtain porous nanomaterials.
[0092] The weight ratio of cyanuric chloride, 2,5-diamino-benzo-dithiazole, triethanolamine and N,N-dimethylformamide is 1:2.7:2.2:65.
[0093] (2) Obtaining adhesive reinforcing agent: The porous nanomaterial, latex powder and 3-amino-2,2-dimethylpropionamide are mixed in a weight ratio of 1:0.65:0.4 to obtain adhesive reinforcing agent.
[0094] The latex powder is an acrylic copolymer with an average particle size of 0.3 μm.
[0095] Example 6
[0096] A tile adhesive and its preparation method, comprising the following steps:
[0097] The difference from Example 3 is that:
[0098] (1) Obtaining porous nanomaterials: 2,5-diamino-benzo-dithiazole was added to the reactor. Under stirring, N,N-dimethylformamide and triethanolamine were added to the reactor to form a dispersion. After ultrasonic treatment of the dispersion for 15 min, cyanuric chloride was added and ultrasonic treatment was performed again for 20 min to obtain the slurry to be reacted. The slurry to be reacted was reacted at 130℃ for 14 h to obtain crude porous nanomaterials. The crude porous nanomaterials were centrifuged to obtain precipitates. The precipitates were washed alternately with deionized water and ethanol and centrifuged 3-5 times. The washed precipitates were freeze-dried to obtain porous nanomaterials.
[0099] The weight ratio of cyanuric chloride, 2,5-diamino-benzo-dithiazole, triethanolamine and N,N-dimethylformamide is 1:3:2.5:80.
[0100] (2) Obtaining adhesive reinforcing agent: The porous nanomaterial, latex powder and 3-amino-2,2-dimethylpropionamide are mixed in a weight ratio of 1:0.8:0.6 to obtain adhesive reinforcing agent.
[0101] The latex powder is an acrylic copolymer with an average particle size of 0.4 μm.
[0102] Comparative Example 1
[0103] A tile adhesive and its preparation method, comprising the following steps:
[0104] The difference from Example 5 is that:
[0105] (3) Obtaining tile adhesive: The amounts of each component are as follows: 57 parts by weight of quartz sand, 41 parts by weight of 42.5R ordinary silicate cement, 2.2 parts by weight of fly ash, 1 part by weight of workability enhancer, 0.7 parts by weight of early strength agent, 0.6 parts by weight of cellulose ether, 0.08 parts by weight of magnesium aluminum silicate, 0.06 parts by weight of starch ether, and 0.02 parts by weight of adhesive enhancer.
[0106] Comparative Example 2
[0107] A tile adhesive and its preparation method, comprising the following steps:
[0108] The difference from Example 5 is that:
[0109] (3) Obtaining tile adhesive: The amounts of each component are as follows: 57 parts by weight of quartz sand, 41 parts by weight of 42.5R ordinary silicate cement, 2.2 parts by weight of fly ash, 1 part by weight of workability enhancer, 0.7 parts by weight of early strength agent, 0.6 parts by weight of cellulose ether, 0.08 parts by weight of magnesium aluminum silicate, 0.06 parts by weight of starch ether, and 0.08 parts by weight of adhesive enhancer.
[0110] Comparative Example 3
[0111] A tile adhesive and its preparation method, comprising the following steps:
[0112] The difference from Example 5 is that:
[0113] (2) Obtaining the adhesive reinforcing agent: The adhesive reinforcing agent is obtained by mixing latex powder and 3-amino-2,2-dimethylpropionamide in a weight ratio of 0.65:0.4. The adhesive reinforcing agent does not contain porous nanomaterials.
[0114] Comparative Example 4
[0115] A tile adhesive and its preparation method, comprising the following steps:
[0116] The difference from Example 5 is that:
[0117] (2) Obtaining the adhesive reinforcing agent: The porous nanomaterial and latex powder are mixed in a weight ratio of 1:0.65 to obtain the adhesive reinforcing agent. The adhesive reinforcing agent does not contain 3-amino-2,2-dimethylpropionamide.
[0118] Experimental Example 1
[0119] The tensile bond strength, tensile bond strength after immersion in water, tensile bond strength after heat aging, tensile bond strength after freeze-thaw cycles, and tensile bond strength after drying time ≥20 min of the tile adhesives prepared using the schemes provided in Examples 1 to 6 and Comparative Examples 1 to 4 were tested. At least 3 parallel experiments were set up for each group, and the average value was taken. The results are shown in Table 1.
[0120] The testing standard is JC / T547-2017, "Ceramic Wall and Floor Tile Adhesives".
[0121] Table 1
[0122]
[0123] As shown in Table 1, the tile adhesives produced in Examples 1 to 6 exhibit significantly improved bonding strength compared to Comparative Examples 1 to 4. In Examples 1 to 6, the tile adhesives, in addition to containing ordinary silicate cement, quartz sand aggregate, and fly ash as the main adhesive components, also include an early-strength agent to improve the early mechanical properties of the tile adhesive, facilitating early bonding between the adhesive and the substrate and accelerating construction. Cellulose ether is also added to further enhance the adhesive properties. Table 1 shows that the tensile bond strength after heat aging and the tensile bond strength after freeze-thaw cycles in Examples 1 to 6 are significantly higher than those in Comparative Examples 1 to 4. This is because the addition of an adhesive enhancer further improves the adhesiveness of the tile adhesive and significantly improves the bond strength when the tile adhesive undergoes thermal expansion and contraction at different temperatures. The adhesive reinforcing agent includes latex powder, 3-amino-2,2-dimethylpropionamide, and porous nanomaterials. After adding the porous nanomaterials, the components in the tile adhesive enter the pores of the nanomaterials. The interwoven network structure connects and binds the components, making them form a cohesive whole. When the external temperature changes, the tile adhesive expands and contracts due to temperature variations. The numerous pores effectively accommodate components with high coefficients of thermal expansion. Simultaneously, the interwoven network structure of the porous nanomaterials disperses the stress generated by thermal expansion and contraction, acting as a buffer between components with different coefficients of thermal expansion. This prevents cracking or even detachment of the tile adhesive caused by varying stresses resulting from the thermal expansion and contraction of different components. The addition of porous nanomaterials disperses and buffers the stress generated by temperature changes in each component, improving both the adhesion and adaptability of the tile adhesive to different temperature environments, thus giving it wide applicability. 3-Amino-2,2-dimethylpropionamide provides amide and amino groups, and the nitrogen atom in it has good activity. It can react with the active groups in porous nanomaterials, ordinary silicate cement, quartz sand aggregate, fly ash, and latex powder, respectively. This can further improve the connection between ordinary silicate cement, quartz sand aggregate, fly ash, latex powder and porous nanomaterials, so that each component can enter the pores of porous nanomaterials and also adsorb on the surface of porous nanomaterials. This improves the connection between the components of tile adhesive, thereby improving the overall adhesion of tile adhesive. It also improves the dispersion and buffering of internal stress generated by the components of tile adhesive during temperature changes by porous nanomaterials, further preventing cracking or detachment of tile adhesive.
[0124] Compared to Comparative Examples 1 and 2, Examples 1 to 6 demonstrate that while the addition of adhesive reinforcing agents is beneficial for improving the tensile bond strength of tile adhesive after thermal aging and after freeze-thaw cycles, the amount of adhesive reinforcing agent added should be within a suitable range. Adding too much or too little will not significantly improve the bond strength of the tile adhesive at different temperatures. Therefore, the amount of adhesive reinforcing agent added in this application is the optimal ratio.
[0125] Compared to Comparative Examples 3 and 4, Examples 1 to 6 show that the porous nanomaterials and 3-amino-2,2-dimethylpropionamide added to the adhesive reinforcing agent work synergistically. The porous structure has strong adsorption properties, adsorbing ordinary silicate cement, quartz sand aggregate, fly ash, and latex powder in the tile adhesive into the pores and on the surface. This allows these particles to fill the pores of the porous nanomaterials, enabling the components in the tile adhesive to bond together. Furthermore, the porous nanomaterials play a cohesive role in the various components. 3-amino-2,2-dimethylpropionamide reacts with... The porous nanomaterials react with the active groups in ordinary silicate cement, quartz sand aggregate, fly ash, and latex powder, thereby further improving the connection between the ordinary silicate cement, quartz sand aggregate, fly ash, latex powder, and porous nanomaterials. This allows each component to enter the pores of the porous nanomaterials and also adsorb onto the surface of the porous nanomaterials, improving the connection between the components of the tile adhesive. This, in turn, improves the overall adhesion of the tile adhesive and enhances the dispersion and buffering of internal stress generated by the components of the tile adhesive during temperature changes by the porous nanomaterials, further preventing cracking or detachment of the tile adhesive.
[0126] Experiment Example 2
[0127] The toxicity of the tile adhesive prepared using the scheme provided in Example 5 above was tested. At least three parallel experiments were set up for each group, and the average value was taken.
[0128] The testing standard is: Radionuclide detection (including internal and external exposure indices): Class A Decoration and Building Materials GB 6566-2010;
[0129] Free formaldehyde testing: GB 18583-2008, "Limits of Hazardous Substances in Adhesives for Interior Decoration and Renovation Materials".
[0130] Hexavalent chromium content: GB / T26125-2011 "Determination of Six Restricted Substances (Lead, Mercury, Cadmium, Hexavalent Chromium, Polybrominated Biphenyls and Polybrominated Diphenyl Ethers) in Electronic and Electrical Products"
[0131] The test results are as follows: In the detection of radionuclides, the internal exposure index I... Ra The external radiation index (I) is 0.1, far below the standard requirement of 1.0. rThe value was 0.2, which is lower than the standard requirement of 1.3, and neither free formaldehyde nor hexavalent chromium was detected, indicating that the tile adhesive provided in this application is environmentally friendly and non-toxic, and can be used in more places.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A method for preparing tile adhesive, characterized in that, The preparation method includes the following steps: (1) Obtaining porous nanomaterials: 2,5-diamino-benzo-dithiazole is added to the reaction vessel. Under stirring, N,N-dimethylformamide and triethanolamine are added to the reaction vessel to form a dispersion. The dispersion is ultrasonically treated for 10-15 min, then cyanuric chloride is added and ultrasonically treated again for 10-20 min to obtain the slurry to be reacted. The slurry to be reacted is reacted at a temperature of 90-130℃ for 10-14 h to obtain crude porous nanomaterials. The crude porous nanomaterials are washed multiple times to obtain the porous nanomaterials. (2) Obtaining adhesive reinforcing agent: The porous nanomaterial, latex powder and 3-amino-2,2-dimethylpropionamide are mixed in a weight ratio to obtain the adhesive reinforcing agent; (3) Obtaining tile adhesive: Quartz sand, ordinary silicate cement, fly ash, workability enhancer, early strength agent, cellulose ether, magnesium aluminum silicate, starch ether and adhesive enhancer are mixed according to the weight parts for 5-10 minutes to obtain the tile adhesive; The tile adhesive comprises the following components in parts by weight: 50-60 parts quartz sand, 38-42 parts ordinary silicate cement, 1.5-2.5 parts fly ash, 0.8-1.2 parts workability enhancer, 0.5-0.8 parts early strength agent, 0.2-0.8 parts cellulose ether, 0.04-0.1 parts magnesium aluminum silicate, 0.04-0.06 parts starch ether, and 0.03-0.07 parts adhesive enhancer; The adhesive reinforcing agent comprises latex powder, 3-amino-2,2-dimethylpropionamide, and porous nanomaterials in a weight ratio of 1:0.5-0.8:0.3-0.
6.
2. The method for preparing tile adhesive according to claim 1, characterized in that, The quartz sand includes quartz sand with a fineness of 30-50 mesh and quartz sand with a fineness of 60-80 mesh, and the weight ratio of the 30-50 mesh quartz sand to the 60-80 mesh quartz sand is 0.75-1:
1.
3. The method for preparing tile adhesive according to claim 1, characterized in that, The ordinary silicate cement is 42.5R ordinary silicate cement.
4. The method for preparing tile adhesive according to claim 1, characterized in that, The cellulose ether is one or more of methyl cellulose ether, carboxymethyl cellulose ether, carboxypropyl methyl cellulose ether, or carboxyethyl cellulose ether.
5. The method for preparing tile adhesive according to any one of claims 1-4, characterized in that, The workability enhancer comprises lignocellulose and sodium gluconate in a weight ratio of 1:0.7-1.
6. The method for preparing tile adhesive according to claim 5, characterized in that, The early strength agent is calcium formate, calcium chloride, or triethanolamine.
7. The method for preparing tile adhesive according to claim 1, characterized in that, The weight ratio of the cyanuric chloride, the 2,5-diamino-benzo-dithiazole, the triethanolamine, and the N,N-dimethylformamide is 1:2.5-3:2.0-2.5:50-80.
8. The method for preparing tile adhesive according to claim 1, characterized in that, In the preparation step of the porous nanomaterial, the crude porous nanomaterial is washed multiple times, including: The crude porous nanomaterial is centrifuged to obtain a precipitate. The precipitate is washed alternately with deionized water and ethanol and centrifuged 3-5 times. The washed precipitate is then freeze-dried to obtain the porous nanomaterial.
9. The method for preparing tile adhesive according to claim 8, characterized in that, The average particle size of the latex powder is 0.2-0.4 μm.
10. A type of tile adhesive, characterized in that, It is obtained according to the preparation method described in any one of claims 1-9 above.
Citation Information
Patent Citations
Single-component ceramic tile adhesive with good thermal aging performance and preparation method of single-component ceramic tile adhesive
CN113173759A
High-performance ceramic tile adhesive and preparation method thereof
CN116496035A